IDENTIFIKASI MOLEKULER BAKTERI PENGHASIL ENZIM L-ASPARAGINASE DARI ALGA COKLAT SARGASSUM sp - Mashuri Masri (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2014)
Molecular Identification of bacterial L-asparaginase activity from Sargassum sp were isolated from Barrang Lompo Island South Sulawesi in 2013. Among them three bacterial strains exhibiting glutaminase free L-asparaginase activity were identified as Pseudomonas putida, Enterobacter asburine dan Marinobacter arcticus on the basis of 16S rRNA gene sequencing. The Highest Max Score 1358 and Query Cover 98 % were Pseudomonas putida furthermore identified as bacterial L-asparaginase activity from Sargassum sp. Pseudomonas putida has Identities 756/765 (99%) with 778 bp Query length, Query cover 98% and Gaps 5/765 (0%).